Color - Wohl, Michael (Peachpit Press, 2008)
A manual for using Color, a computer application for digital video editing.
Print version record
Keywords: Final cut (Electronic resource); Digital video -- Editing -- Data processing; Image processing -- Digital techniques; Color computer graphics; Vidéo numérique; Montage; Informatique; Traitement d'images; Techniques numériques; Infographie couleur; digital imaging; Digital video; Editing; Data processing; Image processing; Digital techniques